Eleco: una prueba para el nível a2 elaborada teniendo en cuenta algunos aspectos de la variedad lingüística y cultural de Colombia - Quevedo Romero, Leidy Marcela (Universidad Antonio Nariño, 2024)
The present document has the purpose of revealing the process of the creation of a proficiency exam for A2 level of Spanish as a Second Language Colombia. During the material´s creation process, the stages of characterization, development and validation were taken into account. In the first stage, a process of questioning took place about the exams that were used to certify the level of foreign people who are interested about learning Spanish in Colombia.